Correlation of CTNNB1 mutation status with progression arrest rate in RECIST progressive desmoid-type fibromatosis treated with imatinib: translational research results from a phase 2 study of the German Interdisciplinary Sarcoma Group (GISG-01) - Kasper, Bernd; Hohenberger, Peter (Annals of surgical oncology, 2016)
Background: CTNNB1 gene mutations are the molecular key events in the majority of sporadic desmoid-type fibromatosis (DF). The specific S45F mutation has been reported to be associated with a more aggressive clinical course in DF. For the current study, the CTNNB1 mutation status was analyzed in DF samples from the prospective German Interdisciplinary Sarcoma Group (GISG) phase 2 study evaluating imatinib to induce progression arrest in DF Response Evaluation Criteria In Solid Tumors (RECIST) progressive patients. Methods: Thirty-seven patients were treated with a planned dose of imatinib 800 mg daily over 2 years (NCT01137916). The progression arrest rate (PAR) after 6 months of treatment was the primary endpoint of the study. CTNNB1 exon 3 mutation status was analyzed using Sanger sequencing. Results: Thirty-three (97 %) of 34 patients reaching the primary endpoint were evaluable for CTNNB1 mutation exon 3 status. T41A mutations accounted for 30.3 % of the study samples and S45 mutations for 48.5 %, whereas CTNNB1 wild-type status was found in 21.2 %. The respective PAR at 6 months was 70, 81, and 43 %. Patients harboring CTNNB1 mutations demonstrated a higher PAR compared to wild-type DF. There was a statistically significant difference comparing patients with S45F mutations (85 % PAR) versus wild-type status (p = 0.05). Conclusions: Mutations at position S45 were overrepresented in the GISG-01 trial recruiting RECIST progressive patients only. The positive correlation of CTNNB1 mutation status with the progression arrest rate after imatinib therapy supports the idea of a potential predictive impact of the mutation status on DF treatment decision making.